THE STORY OF YEXIAN AS THE INTERSECTION OF UNIVERSAL ALGORITHMS THEMATIC. - ČECHOVÁ, Mariana (Porównania, 2015)
The paper pre-sents the synthesis and findings of the author’s long-term study and research concerning the thematic analogies between the fairy tale type 510A and other archnarratives (H. Bayley, R. D. Jameson, M. R. Cox, A. B. Rooth, F. Beauchamp, V. Mair, A. Waley, C. Reed, etc.). The findings are further supplemented with new connections and observations. The core of the exposition is based on the first recorded story of the Cinderella cycle (the story of Yexian, the Chinese prov-ince Guangxi, ca. A.D. 850). The focus of the paper is mostly on the Eastern arch-narratives: the Buddhist texts Dasharathajataka (5th–1st century B.C.) and the Lotus Sūtra (the myths about Guanyin, 1st century A.D.); the Hindu texts the Ramayana (Valmiki’s poem, ca. 500 B.C.) and epics about Bubo and Manu and the fish (about 800 B.C.); the Chinese texts such as A Song of Unending Sorrow (806) and Journey to the West (16th century), a Japanese story Ochikubo Monogatari (ca. 970) and the solar myths (Egyptian, Sumerian, Akkadian, Gnostic and Judeo-Christian).